Epoxy structure adhesive for bonding organic glass

By using two-component epoxy structural adhesives, sulfur-containing polymers and amine compounds containing epoxy end groups are used to solve the problem of low bonding strength of epoxy resin adhesives to plexiglass, and its adhesive properties are significantly improved. Durability.

CN119490810APending Publication Date: 2025-02-21CHINA SPECIAL TYPE FLIER RES INST +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411420650.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The low bonding strength of existing epoxy resin adhesives to plexiglass limits their use in certain applications.

Method used

A two-component epoxy structural adhesive is used, wherein the A component includes an epoxy resin and a sulfur-containing polymer containing epoxy end groups, and the B component includes an amine compound. The sulfur-containing polymer containing epoxy end groups is prepared from a monoolefin compound containing epoxy group and a compound of a double-terminal thiol and a vinyl group-containing organosilicon compound.

Benefits of technology

It significantly improves the adhesive properties of epoxy adhesives to plexiglass substrates, and improves its resistance to dynamic fatigue, out-of-surface impact, humidity and heat aging and salt spray aging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005080677080000071
    Figure BDA0005080677080000071
  • Figure BDA0005080677080000081
    Figure BDA0005080677080000081
Patent Text Reader

Abstract

The invention discloses a bi-component epoxy adhesive. A component A comprises epoxy resin and a sulfur-containing polymer containing an epoxy end group; the component B comprises an amine compound; wherein the sulfur-containing polymer containing the epoxy end group is prepared from an epoxy group-containing monoolefine compound and a precursor polymer, and the precursor polymer is prepared from a double-end thiol compound and a vinyl-containing organosilicon compound. The adhesive property of the epoxy adhesive on an organic glass substrate is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of epoxy adhesives, and in particular relates to an epoxy structural adhesive for bonding organic glass. Background Art

[0002] Epoxy resin adhesives have become an important type of adhesive due to their high bonding strength, wide adaptability to substrates, and excellent environmental resistance. In recent years, high-strength lightweight alloys, carbon fiber composite materials, and engineering plastics have been widely used in the fields of automobiles, rails, and aviation. These parts often use bonding processes to form a complete body or component. The epoxy glue used for bonding usually requires the use of polysulfide rubber or nitrile rubber, nanoparticles, and other toughening and modification technologies to make the bonded joints have high toughness, good resistance to mechanical vibration or impact, and good resistance to environmental aging.

[0003] However, polysulfide rubber contains thiol terminal groups, which have a strong odor and low disulfide bond energy, resulting in poor high temperature resistance. In addition, it has low bonding strength for low surface energy engineering plastics such as plexiglass and ABS, which limits its further use. Summary of the invention

[0004] Purpose of the Invention

[0005] In order to solve the problem that the existing epoxy resin adhesive has low bonding strength to organic glass, the present invention provides an epoxy structural adhesive for bonding organic glass.

[0006] Inventing technical solutions

[0007] An epoxy structural adhesive for bonding organic glass, component A comprises: epoxy resin, sulfur-containing polymer containing epoxy terminal groups; component B comprises: amine compounds; wherein the sulfur-containing polymer containing epoxy terminal groups is prepared from a monoolefin compound containing epoxy groups and a precursor polymer, and the precursor polymer is prepared from a double-terminal thiol compound and a vinyl-containing organosilicon compound.

[0008] Preferably, the epoxy monoolefin compound is selected from glycidyl ether containing a monoethylenically unsaturated double bond, glycidyl ester containing a monoethylenically unsaturated double bond, or a combination thereof.

[0009] Preferably, the amine compound is selected from polyamide-modified amines, aliphatic compound-modified amines, alicyclic compound-modified amines or combinations thereof.

[0010] Preferably, the epoxy resin is selected from bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol H epoxy resin or a combination thereof.

[0011] Preferably, the weight ratio of the epoxy resin to the epoxy-terminated sulfur-containing polymer is 0.1-14:1.

[0012] Preferably, the ratio of the amine compound to the epoxy resin is theoretically calculated based on a ratio of epoxy equivalent to active hydrogen equivalent of the amine compound of 1:1.

[0013] Preferably, the vinyl-containing organosilicon compound is selected from one or any combination of divinyltetramethyldisiloxane and low-viscosity vinyl-terminated silicone oil; the low-viscosity vinyl-terminated silicone oil is CH2=CH-Si(CH3)2O[(CH3)2SiO] n (CH3)2Si-CH=CH2 and / or CH2=CH[(CH3)(C6H5)SiO] m -[(CH3)2SiO] x -Si(CH3)2CH=CH2, n is 1-100, m is 1-10, and x is 1-10.

[0014] Preferably, the double-terminal thiol compound is selected from one or any combination of HS-CH2CH(CH3)-S-CH(CH3)CH2-SH, HS-CH(CH3)CH2-S-CH2-CH(CH3)-SH, HS-CH2-CH2-S-CH2-CH2-SH, HSCH2-S-CH2-SH, HSCH2-S-CH2-SH, HS(CH2CH2NH)5(CH2)5SH, and HS(CH2CH2O)5(CH2)5SH.

[0015] Preferably, it also includes a reinforcing filler, which is selected from one or any combination of silica powder, kaolin, bentonite, calcium carbonate, titanium dioxide, and pigment carbon black.

[0016] Preferably, the composition further comprises an auxiliary agent, which comprises a silane coupling agent and an epoxy-containing reactive diluent.

[0017] Advantages of the present invention:

[0018] 1) Improved the bonding performance of epoxy adhesive to organic glass substrate.

[0019] 2) It has good dynamic fatigue resistance and out-of-plane impact resistance, as well as good resistance to moisture and heat aging, salt spray aging, etc.

[0020] 3) It can be applied to the structural or semi-structural connection between organic glass substrates and substrates such as metal and carbon fiber composite materials. DETAILED DESCRIPTION

[0021] The present invention is achieved through the following technical solutions.

[0022] The invention discloses an epoxy structural adhesive for bonding organic glass. The component A comprises: epoxy resin and sulfur-containing polymer containing epoxy terminal groups; and the component B comprises: an amine compound curing agent.

[0023] The epoxy-terminated sulfur-containing polymer used in the present application is a sulfur- and silicone-containing epoxy-terminated polymer, which is prepared from an epoxy-containing monoolefin compound and a precursor polymer, wherein the precursor polymer is prepared from a double-terminal thiol compound and a vinyl-containing organosilicon compound.

[0024] The epoxy monoolefin compound has an ethylenically unsaturated carbon-carbon double bond, and can be selected from, for example, glycidyl ethers containing monoethylenically unsaturated double bonds, glycidyl esters containing monoethylenically unsaturated double bonds, or combinations thereof. For example, the epoxy monoolefin compound can be selected from propylene glycidyl ether, 1,2-epoxy-4-vinylcyclohexane, 1,2-epoxy-5-hexene, butadiene monoepoxide, glycidyl methacrylate, or combinations thereof.

[0025] The vinyl-containing organosilicon compound contains two olefinically unsaturated carbon-carbon double bonds, and can be selected from, for example, divinyltetramethyldisiloxane, a low-viscosity vinyl-terminated silicone oil, or any combination thereof; the low-viscosity vinyl-terminated silicone oil is CH2=CH-Si(CH3)2O[(CH3)2SiO] n (CH3)2Si-CH=CH2 and / or CH2=CH[(CH3)(C6H5)SiO] m -[(CH3)2SiO] x -Si(CH3)2CH=CH2, n is 1-100, m is 1-10, and x is 1-10.

[0026] The double-terminal thiol compound contains two thiol groups and can be selected from one or any combination of HS-CH2CH(CH3)-S-CH(CH3)CH2-SH, HS-CH(CH3)CH2-S-CH2-CH(CH3)-SH, HS-CH2-CH2-S-CH2-CH2-SH, HSCH2-S-CH2-SH, HSCH2-S-CH2-SH, HS(CH2CH2NH)5(CH2)5SH, and HS(CH2CH2O)5(CH2)5SH.

[0027] The precursor polymer is a product obtained by a thiol / vinyl addition reaction between a double-terminal thiol compound and a vinyl-containing organosilicon compound. The polymerization reaction of the epoxy olefin compound and the precursor polymer is an addition polymerization reaction between the thiol group and the carbon-carbon double bond. Usually, the epoxy-containing monoolefin compound and the precursor polymer can be reacted at 60-100°C under the action of a free radical addition reaction catalyst such as an azo compound to obtain a sulfur-containing polymer containing an epoxy terminal group. The viscosity of the sulfur-containing polymer containing an epoxy terminal group (at 25°C) is 100-1000000 mPa·s. The sulfur-containing polymer containing epoxy groups in the present application reduces the odor of the thiol group and improves the high temperature resistance due to the introduction of siloxane groups and sulfur chains. The introduction of epoxy groups can carry out epoxy co-crosslinking curing reaction, and the introduced flexible organosilicon chain molecular structure improves the flexibility and out-of-plane impact resistance of the epoxy resin.

[0028] The epoxy adhesive of the present invention introduces a polar -S-structure with a relatively high bond energy (227 kJ / mol) by using the sulfur-containing polymer containing epoxy end groups of the present application, which can significantly improve the high temperature resistance of the epoxy adhesive. The flexibility of the epoxy adhesive can be improved through the chain links of the siloxane structure. This structure can significantly improve the bonding performance to low surface energy materials such as organic glass.

[0029] The two-component epoxy adhesive of the present application contains an epoxy resin. The epoxy resin is a common bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol H epoxy resin or a combination thereof. In one embodiment, the mass ratio of the epoxy resin to the sulfur-containing polymer containing epoxy end groups is 0.1-14:1, preferably 1-5:1.

[0030] The two-component epoxy adhesive of the present application contains an amine compound curing agent, which is selected from polyamide modified amines, aliphatic compound modified amines, alicyclic compound modified amines or combinations thereof. In one embodiment, the amount of the amine compound curing agent is calculated based on the equivalent moles of the active hydrogen of the amine group and the equivalent of the epoxy group.

[0031] The two-component epoxy adhesive of the present application further comprises a reinforcing filler. The reinforcing filler may be selected from one or any combination of silica powder, kaolin, bentonite, calcium carbonate, titanium dioxide, and pigment carbon black. In one embodiment, the weight of the reinforcing filler is 10-200wt% of the total weight of the epoxy resin, the sulfur-containing polymer containing epoxy end groups, and the amine compound curing agent, such as 10-150wt%.

[0032] The two-component epoxy adhesive of the present application further comprises an auxiliary agent. The auxiliary agent may include a silane coupling agent, an epoxy-containing reactive diluent, other toughening agents, etc. These auxiliary agents may be various auxiliary agents commonly used in the art, which will not be described in detail here.

[0033] The two-component epoxy adhesive of the present application comprises an epoxy resin, a sulfur-containing polymer with epoxy end groups, an amine compound curing agent, and optional reinforcing fillers and other additives. The sulfur-containing polymer containing epoxy end groups has good compatibility with the epoxy resin, and can be cross-linked with the curing agent for a co-crosslinking curing reaction, which can significantly improve the flexibility of the epoxy adhesive, and improve the bonding performance to substrate materials such as organic glass, which is conducive to improving the bonding to plastic materials, and is particularly suitable as a structural adhesive for organic glass, composite materials and alloy materials. The two-component epoxy adhesive has good construction performance (adjustable viscosity or thixotropic). When used, the two components are mixed evenly, and can be cured at room temperature or heated to accelerate curing, and the construction is convenient. The two-component epoxy adhesive has a long storage time and adjustable curing conditions. It can usually be cured at room temperature, usually completely cured in 3-7 days, and can also be cured at 40-100°C, with a curing time of about 20-100min to complete curing.

[0034] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. The chemicals described therein are all commercially available products unless otherwise specified.

[0035] The epoxy value of epoxy resin is determined by hydrochloric acid acetone method; the determination method of vinyl content refers to HG / T3312-2000 "110 methyl vinyl silicone rubber"; the determination method of tensile shear strength refers to GB / T7124-2008 "Determination of tensile shear strength of adhesives"; high temperature and high humidity test: test according to GB / T2423.50-2012 constant heat and humidity component accelerated aging test

[0036] Synthesis Example 1

[0037] Under nitrogen protection, 91 g of ethanedithiol and 686 g of vinyl silicone oil (CH2=CH-Si(CH3)2O[(CH3)2SiO] n (CH3)2Si-CH=CH2, n is 8, viscosity is 10mPa·s, vinyl content is 6.9%) and solvent toluene are fully mixed, heated to 50°C, stirred for 1h, and then 0.1g AIBN is added. The reaction is carried out under closed conditions for 3h. During this period, the vinyl content is measured. When the vinyl content drops to the lowest, 25g of glycidyl methacrylate is added. The closed reaction is maintained for 3h. After the reaction is completed, the reaction liquid is removed from unreacted monomers and solvents under vacuum conditions of 110°C and 1kPa to obtain a light yellow transparent liquid which is an epoxy-terminated sulfur-containing silicone epoxy polymer.

[0038] The epoxy-terminated sulfur-containing organosilicon epoxy polymer prepared in this example has a viscosity of 36000 mPa·s, a S element mass percentage content of 8% in the polymer, and a mass content of epoxy groups of 0.72% (100 g contains 0.3 mol of epoxy groups).

[0039] Synthesis Example 2

[0040] Under nitrogen protection, 388g of a molecular formula such as HS(CH2CH2NH)5(CH2)5SH, 190g of divinyltetramethyldisiloxane and solvent toluene were fully stirred and mixed, heated to 50°C, stirred for 1h, and then 0.1g of AIBN was added to react under closed conditions for 3h, during which the vinyl content was measured. When the vinyl content dropped to the lowest, 25g of 1,2-epoxy-4-vinylcyclohexane and 0.1g of DMPA were slowly added dropwise to the above reaction solution to maintain a closed reaction for 3h. After the reaction was completed, the reaction solution was removed from unreacted monomers and solvents under vacuum conditions of 110°C and 1kPa to obtain a light yellow transparent liquid that was epoxy-terminated sulfur-containing silicone epoxy polymer.

[0041] The epoxy-terminated sulfur-containing organosilicon epoxy polymer prepared in this example has a viscosity of 18600 mPa·s, a S element mass percentage content of 18.4% in the polymer, and a mass content of epoxy groups of 0.88%.

[0042] Synthesis Example 3

[0043] Under nitrogen protection, 90g of molecular formula such as HS-CH2CH(CH3)-S-CH(CH3)CH2-SH and 423.8g of terminal vinyl phenyl silicone oil were added.

[0044] (CH2=CH-Si(CH3)2O[(CH3)2SiO] n [(CH3)(C6H5)SiO] m (CH3)2Si-CH=CH2, n is 5, m is 3, viscosity 50mPa·s, vinyl content 6%) is fully mixed, heated to 50°C, stirred for 1h, and then 0.1g AIBN is added to react under closed conditions for 3h, during which the vinyl content is measured. When the vinyl content drops to the lowest, solvent toluene is added and stirred thoroughly to dissolve, and then 25g 3,4-epoxy-1-butene is added to the round-bottom flask. 0.1g DMPA is premixed into the solvent and then slowly added dropwise to the above reaction solution to maintain a closed reaction for 3h. After the reaction is completed, the reaction solution is removed from the unreacted monomers and solvent under vacuum conditions of 110°C and 1kPa to obtain a light yellow transparent liquid that is an epoxy-terminated sulfur-containing silicone epoxy polymer.

[0045] The epoxy-terminated sulfur-containing organosilicon epoxy polymer prepared in this example has a viscosity of 87000 mPa·s, a S element mass percentage content of 8.9% in the polymer, and a mass content of epoxy groups of 0.3%.

[0046] Example 1

[0047] The two-component epoxy adhesive of this embodiment is composed of the following parts by weight: Component A: 10 parts of the epoxy-terminated sulfur-containing silicone epoxy polymer prepared in Synthesis Example 1, 30 parts of epoxy resin E51, 1 part of silane coupling agent KH560, 10 parts of heavy calcium carbonate, and 10 parts of titanium dioxide; Component B: 10 parts of polyamide curing agent, 5 parts of fatty amine curing agent, 1 part of tertiary amine accelerator, 20 parts of titanium dioxide, and 0.1 part of blue pigment.

[0048] The epoxy structural adhesive of this embodiment is prepared by the following steps: the raw materials in components A and B are respectively added into a double planetary stirring kettle, vacuumed and stirred to mix evenly, and after vacuuming and stirring for 30 minutes, components A and B of the epoxy adhesive are obtained, and then the two components of the adhesive are transferred to a dry and clean container for standby use.

[0049] Example 2

[0050] The two-component epoxy adhesive of this embodiment is composed of the following parts by weight: component A: 30 parts of the epoxy-terminated sulfur-containing silicone epoxy polymer prepared in Synthesis Example 2, 30 parts of epoxy resin E44, 1 part of silane coupling agent KH560, 10 parts of light calcium carbonate, and 1 part of fumed silica; component B: 15 parts of polyamide curing agent, 2 parts of fatty amine curing agent, 11 parts of silicon powder, and 0.1 part of black pigment.

[0051] The epoxy structural adhesive of this embodiment is prepared by the following steps: the raw materials in components A and B are respectively added into a double planetary stirring kettle, vacuumed and stirred to mix evenly, and after vacuuming and stirring for 30 minutes, components A and B of the epoxy adhesive are obtained, and then the two components of the adhesive are transferred to a dry and clean container for standby use.

[0052] Example 3

[0053] The two-component epoxy adhesive of this embodiment is composed of the following parts by weight: Component A: 60 parts of the epoxy-terminated sulfur-containing silicone epoxy polymer prepared in Synthesis Example 3, 20 parts of epoxy resin 170, 1 part of silane coupling agent KH560, 10 parts of silicon micropowder, and 10 parts of kaolin; Component B: 3 parts of polyamide curing agent, 10 parts of fatty amine curing agent, 2 parts of alicyclic curing agent, 0.5 parts of tertiary amine accelerator, and 20 parts of titanium dioxide.

[0054] The epoxy structural adhesive of this embodiment is prepared by the following steps: the raw materials in components A and B are respectively added into a double planetary stirring kettle, vacuumed and stirred to mix evenly, and after vacuuming and stirring for 30 minutes, components A and B of the epoxy adhesive are obtained, and then the two components of the adhesive are transferred to a dry and clean container for standby use.

[0055] Comparative Example 1

[0056] The epoxy-modified polysulfide polymer disclosed in patent CN104448314B, specifically the product obtained in Example 1 of patent CN104448314B, is used to replace the epoxy-terminated sulfur-containing silicone polymer obtained in Synthesis Example 3 used in Example 3. The amounts of other raw materials and the preparation method are the same as those in Example 3.

[0057] The epoxy adhesives of the above embodiments and comparative examples were tested, and the results are shown in Table 1.

[0058] Table 1

[0059]

[0060]

[0061] The out-of-plane impact resistance is tested by making the prepared adhesive and the plexiglass substrate sampled and cured according to GB7124. The impact energy is 2.5J and the span of the sample is 5mm. After the impact test, the tensile shear strength test is carried out.

[0062] For the salt spray resistance test, the prepared adhesive and the plexiglass substrate were sampled and cured according to GB7124, and then placed in a salt spray test chamber for salt spray aging test for 20 days. Then, they were left to stand for 24 hours under standard experimental conditions, and then the tensile shear strength test was performed.

[0063] From the data in Table 1, it can be seen that the epoxy adhesive further prepared by using the epoxy-terminated silicone-containing polysulfide polymer described in this patent has significantly improved bonding performance to organic glass substrates, and has better out-of-plane impact resistance and salt spray corrosion aging performance than the adhesive obtained by epoxy-terminated polysulfide polymer without silicone.

[0064] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable technicians familiar with the technical field to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit and essence of the present invention should be included in the protection scope of the present invention. The technology, shape, and structure parts not described in detail in the present invention are all well-known technologies.

Claims

1. An epoxy structural adhesive for bonding organic glass, characterized in that: Component A includes: epoxy resin, sulfur-containing polymer containing epoxy terminal groups; component B includes: amine compounds; wherein the sulfur-containing polymer containing epoxy terminal groups is prepared from a monoolefin compound containing epoxy groups and a precursor polymer, and the precursor polymer is prepared from a double-terminal thiol compound and a vinyl-containing organosilicon compound.

2. The epoxy structural adhesive for bonding organic glass as claimed in claim 1, characterized in that: The epoxy monoolefin compound is selected from the group consisting of glycidyl ether containing a monoethylenically unsaturated double bond, glycidyl ester containing a monoethylenically unsaturated double bond, or a combination thereof.

3. The epoxy structural adhesive for bonding organic glass as claimed in claim 1, characterized in that: The amine compound is selected from polyamide-modified amines, aliphatic compound-modified amines, alicyclic compound-modified amines or combinations thereof.

4. The epoxy structural adhesive for bonding organic glass as claimed in claim 1, characterized in that: The epoxy resin is selected from bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol H epoxy resin or a combination thereof.

5. The epoxy structural adhesive for bonding organic glass as claimed in claim 1, characterized in that: The weight ratio of the epoxy resin to the epoxy-terminated sulfur-containing polymer is 0.1-14:

1.

6. A two-component epoxy adhesive as claimed in claim 1, characterized in that: The ratio of the amine compound to the epoxy resin is theoretically calculated based on the epoxy equivalent to the active hydrogen equivalent of the amine compound being 1:

1.

7. The epoxy structural adhesive for bonding organic glass as claimed in claim 1, characterized in that: The vinyl-containing organosilicon compound is selected from one or any combination of divinyltetramethyldisiloxane and low-viscosity vinyl-terminated silicone oil; the low-viscosity vinyl-terminated silicone oil is CH2=CH-Si(CH3)2O[(CH3)2SiO] n (CH3)2Si-CH=CH2 and / or CH2=CH[(CH3)(C6H5)SiO] m -[(CH3)2SiO] x -Si(CH3)2CH=CH2, n is 1-100, m is 1-10, and x is 1-10.

8. The epoxy structural adhesive for bonding organic glass as claimed in claim 1, characterized in that: The double-terminal thiol compound is selected from one or any combination of HS-CH2CH(CH3)-S-CH(CH3)CH2-SH, HS-CH(CH3)CH2-S-CH2-CH(CH3)-SH, HS-CH2-CH2-S-CH2-CH2-SH, HSCH2-S-CH2-SH, HSCH2-S-CH2-SH, HS(CH2CH2NH)5(CH2)5SH, and HS(CH2CH2O)5(CH2)5SH.

9. The epoxy structural adhesive for bonding organic glass as claimed in claim 1, characterized in that: It also includes reinforcing fillers, which are selected from one or any combination of silica powder, kaolin, bentonite, calcium carbonate, titanium dioxide, and pigment carbon black.

10. The epoxy structural adhesive for bonding organic glass according to claim 1, characterized in that: The invention also comprises auxiliary agents, which include silane coupling agents and reactive diluents containing epoxy groups.

Citation Information

Patent Citations

  • An epoxy-terminated polysulfide polymer, its preparation method and uses, and a room-temperature fast-curing epoxy resin adhesive containing the same.

    CN104448314B